Bonus Question: Does Flexible Incentive Pay Dampen Unemployment Dynamics? - Meghana Gaur; John Grigsby; Jonathon Hazell; Abdoulaye Ndiaye (Institute of Labor Economics (IZA), 2023)
We introduce dynamic incentive contracts into a model of unemployment dynamics and present three results. First, wage cyclicality from incentives does not dampen unemployment dynamics: the response of unemployment to shocks is first-order equivalent in an economy with flexible incentive pay and without bargaining, vis-a-vis an economy with rigid wages. Second, wage cyclicality from bargaining dampens unemployment dynamics through the standard mechanism. Third, our calibrated model suggests 46% of wage cyclicality in the data arises from incentives. A standard model without incentives calibrated to weakly procyclical wages, matches unemployment dynamics in our incentive pay model calibrated to strongly procyclical wages.
Keywords: E24; E32; J41; 330; incentive contracts; unemployment dynamics; wage rigidity